2014
DOI: 10.1152/ajprenal.00647.2013
|View full text |Cite
|
Sign up to set email alerts
|

APOL1 risk variants enhance podocyte necrosis through compromising lysosomal membrane permeability

Abstract: Development of higher rates of nondiabetic glomerulosclerosis (GS) in African Americans has been attributed to two coding sequence variants (G1 and G2) in the APOL1 gene. To date, the cellular function and the role of APOL1 variants (Vs) in GS are still unknown. In this study, we examined the effects of overexpressing wild-type (G0) and kidney disease risk variants (G1 and G2) of APOL1 in human podocytes using a lentivirus expression system. Interestingly, G0 inflicted podocyte injury only at a higher concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
212
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(223 citation statements)
references
References 48 publications
4
212
2
5
Order By: Relevance
“…Furthermore, expression of G0 (wild-type) APOL1 appears to induce programmed cell death, although the exact mechanism has yet to be determined. Prior reports on the main mechanism of APOL1-induced cell death implicate the autophagic pathway ( 19,22 ), while others have shown that APOL1 induces podocyte necrosis by compromising lysosomal membrane permeability ( 25 ). Major goals of the present study were to elucidate the pathway of APOL1-induced cell death, as well as general outcomes of APOL1 expression in liver whether autophagy was involved in the cytotoxicity of APOL1 and its disease variants in our inducible cell lines, we fi rst performed Western blot analysis to examine LC3-II accumulation, a reliable marker of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, expression of G0 (wild-type) APOL1 appears to induce programmed cell death, although the exact mechanism has yet to be determined. Prior reports on the main mechanism of APOL1-induced cell death implicate the autophagic pathway ( 19,22 ), while others have shown that APOL1 induces podocyte necrosis by compromising lysosomal membrane permeability ( 25 ). Major goals of the present study were to elucidate the pathway of APOL1-induced cell death, as well as general outcomes of APOL1 expression in liver whether autophagy was involved in the cytotoxicity of APOL1 and its disease variants in our inducible cell lines, we fi rst performed Western blot analysis to examine LC3-II accumulation, a reliable marker of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study describes the influence of APOL1 risk variants on enhanced podocyte necrosis through compromised lysosomal membrane permeability. 23 Much remains to be explored in this area, including, the full degree of heterogeneous individual glomerular enlargement that the estimate of average V glom disguises, 17,24 and indices of podocyte number and density in the younger and older at-risk subjects 25 in the various APOL1 subgroups. This series is not a resource for the study of kidney disease, because such subjects were deliberately excluded.…”
Section: The Similarity Of Thementioning
confidence: 99%
“…The evidence against a loss-of-function model (in which APOL1 is a protective factor in the kidney) include: (1) APOL1 does not appear to be required for normal kidney function because a human homozygous null individual has been identified with apparently normal kidney function after several years of follow-up, 8,9 (2) the restricted species distribution of the APOL1 gene, 10,11 and (3) evidence for increased cytotoxic effects of G1 and G2 APOL1 when expressed in a variety of model systems. 7,[12][13][14] The bulk of APOL1 is found in the plasma, where it circulates as part of a specialized HDL particle consisting of APOA1, APOL1 and the hemoglobin binding protein HaptoglobinRelated Protein (HPR), which also serves as the receptor for uptake by trypanosomes. 15 A subset of APOL1-HDL has also been shown to bind IgM and forms the distinct lytic factor TLF-2.…”
mentioning
confidence: 99%